PENGARUH PENDIDIKAN DAN PELATIHAN MENENGAH PERKOPERASIAN TERHADAP TUMBUHNYA MINAT BERWIRAUSAHA DITINJAU DARI PARTISIPASI DAN SOFT SKILLS ANGGOTA KOPERASI MAHASISWA UNIVERSITAS NEGERI YOGYAKARTA - Raharjo, Bambang Puji; M.Si, Baedhowi; Sawiji, Hery (Jurnal Pendidikan Insan Mandiri, 2014)
Students are encouraged to become entrepreneur as a career option. By the time they graduate from their study and get their degrees, they are expected to be able to create jobs for themselves and others. Student co-operative has a role in the development and regeneration of entrepreneurship amongst students through attending some particular educations and trainings. The contribution of student co-operative in achieving the interest in entrepreneurship is influenced by the participation and the soft skills of its members. This study aimed to determine the interaction between secondary co-operation education and training, members? participation, and members? soft skills towards the interest in entrepreneurship. The method used in this study was ex-post facto with a quantitative descriptive approach.  The population of the study was taken from the members of Student Co-operative in Universitas Negeri Yogyakarta. Study sample was divided into two groups, which were members who have already attended in education and training program with a total of 70 students collected by purposive sampling, and members who have not been attended in education and training with a total of 70 students taken in quota sampling. Data was collected through questionnaire, documentation, and interviews. This data was analyzed by using three-way ANOVA analysis 2x2x2 factorial.The result of the study showed that: 1) there was a significant difference on the interest in entrepreneurship between members who were attended in the secondary co-operation education and training and members who were not attended in the secondary co-operation education and training, 2) there was no significant difference on the interest in entrepreneurship between active and passive members? participation, 3) there was a significant difference on the interest in entrepreneurship amongst members with high and low soft skills, 4) there was no significant interaction between secondary co-operation education and training and the members? participation towards the interest in entrepreneurship, 5) there was a significant interaction between secondary co-operation education and training and soft skills towards the interest in entrepreneurship, 6) there was a significant interaction between members? participation and soft skills towards the interest in entrepreneurship, 7) there was a significant interaction between secondary co-operation education and training, members? participation and soft skills towards the interest in entrepreneurship.Keywords: education and training, interest in entrepreneurship, member participation, soft skills